PENGARUH KECUKUPAN MODAL, LIKUIDITAS, RISIKO KREDIT, DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PERBANKAN UMUM SWASTA NASIONAL DI BUSA EFEK INDONESIA - Khayrul Astria Setianingrum, Edi Wibowo & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2018)
The purpose of this study is to: 1) analyze the significance of the influence of capital adequacy to profitability, 2) to analyze the significance of the effect of liquidity on profitability, 3) to analyze the significance of the effect of credit risk on profitability, 4) to analyze the significance of the effect of operational efficiency level on profitability, significance of capital adequacy, liquidity, credit risk, and operational efficiency simultaneously to profitability. This type of research use survey, data analysis technique using multiple linear regression analysis with sample of 8 bank with purposive sampling method. Hypothesis testing using t test (partial test), F test (simultaneous test), and test of coefficient of determination (R2). The result of t analysis shows that partially CAR, LDR, and NPL variables have no significant effect on ROA, while BOPO variable has significant effect on ROA. Simultaneously capital adequacy, liquidity, credit risk, and operational efficiency affect the ROA of National Private Private Banking at BEI. The result of (R2) shows that 93,7% variation of profitability variable can be explained by BOPO.Keywords: capital adequacy, liquidity, credit risk, operational efficiency, profitability